Alloy with high yttrium content and preparation method thereof

By using raw materials such as yttrium oxide and modified alumina to prepare alloys with high yttrium content, the problem of poor stability in existing alloys in extreme environments is solved, and high strength, corrosion resistance and good molding performance are achieved.

CN119504231APending Publication Date: 2025-02-25GUANGDONG HUAAO ALLOY NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411683522.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing alloys have poor stability in extreme environments, and excessive addition of yttrium may lead to uneven and incompatible components, affecting overall performance.

Method used

Yttrium oxide and modified alumina are used as the main raw materials, combined with graphite powder, zinc stearate and manganese sulfide, and alloys with high yttrium content are prepared through sintering and shaping processes to improve grain refinement and interface bonding.

Benefits of technology

It improves the tensile strength, densification degree and corrosion resistance of the alloy, reduces the friction between the material and the mold, and enhances the overall performance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148931480000061
    Figure BDA0005148931480000061
  • Figure BDA0005148931480000071
    Figure BDA0005148931480000071
Patent Text Reader

Abstract

The invention discloses an alloy with high yttrium content and a preparation method thereof, and relates to the field of alloys, and the alloy comprises the following raw materials by weight: 80-120 parts of yttrium oxide; 1-3 parts of chromium oxide; 10 to 20 parts of modified aluminum oxide; 1-5 parts of nickel oxide; 1-2 parts of graphite powder; 1-2 parts of zinc stearate; 0.5 to 1.5 parts of manganese sulfide; the modified aluminum oxide is prepared from the following raw materials: titanium dioxide, aluminum oxide, dilute sulphuric acid, sodium metaaluminate, maleic anhydride grafted polypropylene and a silane coupling agent. The method has the effect of improving the tensile strength of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alloys, and in particular to an alloy with a high yttrium content and a preparation method thereof. Background Art

[0002] At present, with the continuous improvement of material performance requirements in modern manufacturing, especially for materials in high-tech industries such as aerospace, automobiles, etc., they must not only have the characteristics of high strength and fatigue resistance, but also be able to maintain good stability in extreme environments; yttrium, as one of the important rare earth elements, shows unique advantages in improving alloy strength, improving alloy heat resistance and wear resistance.

[0003] Existing alloy improvements are usually achieved by adding trace amounts of yttrium. For example, some nickel-based superalloys used in aircraft engine blades will add an appropriate amount of yttrium to improve their antioxidant capacity and thermal stability. However, excessive addition of yttrium may make it difficult to evenly distribute the alloy components, and incompatible reactions may occur between yttrium and other trace elements, affecting the overall performance of the alloy. Summary of the invention

[0004] In order to improve the tensile strength of the alloy, the present application provides an alloy with a high yttrium content and a preparation method thereof.

[0005] In a first aspect, the present application provides an alloy with a high yttrium content using the following technical solution: An alloy with a high yttrium content comprises the following raw materials in parts by weight: 0.8-1.2 parts of yttrium oxide; 20-30 parts of chromium oxide; 10-20 parts of modified aluminum oxide; 30-50 parts of nickel oxide; 1-2 parts of graphite powder; 1-2 parts of zinc stearate; and 0.5-1.5 parts of manganese sulfide. The modified aluminum oxide is prepared from the following raw materials: titanium dioxide, aluminum oxide, dilute sulfuric acid, sodium metaaluminate, maleic anhydride grafted polypropylene and a silane coupling agent.

[0006] By adopting the above technical scheme, the present application uses yttrium oxide and modified alumina as raw materials for the alloy, and the yttrium content in the prepared yttrium alloy is relatively high, which helps to promote grain refinement and improve the strength and densification of the alloy; the main component of graphite powder is carbon, which can improve the strength of the yttrium alloy; the addition of manganese sulfide can help the processing steps after the yttrium alloy is formed, and zinc stearate is used as a lubricant to reduce the friction between the material and the forming mold during the forming process of the yttrium alloy, thereby better improving the density of the yttrium alloy, and various raw materials cooperate with each other to form a yttrium alloy with higher hardness.

[0007] Preferably, the preparation method of the modified alumina is: 10-30 parts of titanium dioxide, 20-60 parts of alumina and 2-8 parts of dilute sulfuric acid are mixed and stirred, and then 5-15 parts of sodium aluminate are added, stirred and calcined, and after cooling, 10-20 parts of maleic anhydride grafted polypropylene and 5-15 parts of silane coupling agent are mixed and stirred, and after drying, the modified alumina is obtained.

[0008] By adopting the above technical scheme, the present application modifies alumina, adds titanium dioxide to alumina, distributes titanium dioxide on the surface of alumina, reduces impurities and defects in the material after calcination, and combines alumina containing titanium dioxide with yttrium oxide. The use of maleic anhydride grafted polypropylene and silane coupling agent improves the interface bonding between the modified alumina and the yttrium aluminum alloy matrix, thereby improving the overall performance of the composite material.

[0009] Preferably, the maleic anhydride grafted polypropylene is modified maleic anhydride grafted polypropylene, and the preparation method of the modified maleic anhydride grafted polypropylene is: 10-20 parts of maleic anhydride grafted polypropylene, 1-3 parts of diisopropylbenzene peroxide, 2-8 parts of dimethyl methyl phosphate and 5-15 parts of ethyl acetate are mixed and stirred, and then 4-8 parts of carbon fiber are added and mixed and stirred, ultrasonicated, filtered and then dried for 12 hours to obtain the modified maleic anhydride grafted polypropylene.

[0010] By adopting the above technical scheme, maleic anhydride grafted polypropylene can be used as an adhesive between yttrium aluminum alloy and carbon fiber to improve the bonding strength of the interface. Dimethyl methylphosphonate and ethyl acetate are used as solvents to help the carbon fiber and maleic anhydride grafted polypropylene to mix and react, so that the carbon fiber can be dispersed in the maleic anhydride grafted polypropylene, thereby allowing the carbon fiber to penetrate into the alloy component and improve the mechanical properties of the yttrium alloy.

[0011] Preferably, the weight ratio of the maleic anhydride grafted polypropylene, carbon fiber and dimethyl methyl phosphate is (3.4-3.8):1:(0.5-0.6).

[0012] By adopting the above technical scheme, when maleic anhydride grafted polypropylene, carbon fiber and dimethyl methyl phosphonate are in a specific weight ratio, maleic anhydride grafted polypropylene can form chemical bonds with the surfaces of aluminum oxide and yttrium oxide, enhance the interfacial bonding force between the raw materials, thereby improving the mechanical properties of the alloy, while maleic anhydride grafted polypropylene also bonds the carbon fiber to the alloy matrix, and dimethyl methyl phosphonate improves the bonding performance of the carbon fiber to the alloy matrix, thereby improving the overall performance of the alloy.

[0013] Preferably, the grafting rate of the modified maleic anhydride grafted polypropylene is 1-1.6%.

[0014] By adopting the above technical scheme, selecting maleic anhydride grafted polypropylene with an appropriate grafting rate helps to improve the compatibility of maleic anhydride grafted polypropylene with carbon fiber. The maleic anhydride group can form chemical bonds with polar surfaces or enhance physical adsorption, thereby improving the adhesion between carbon fiber and alumina, which helps to improve the mechanical properties of yttrium alloy.

[0015] Preferably, the weight ratio of titanium dioxide, modified maleic anhydride grafted polypropylene, sodium aluminate and aluminum oxide is 1: (0.8-0.9): (0.3-0.4): (2.5-2.8).

[0016] By adopting the above technical scheme, when titanium dioxide, modified maleic anhydride grafted polypropylene, sodium aluminate and aluminum oxide are in a specific weight ratio, the four work together to improve the interface bonding inside the yttrium alloy, promote the refinement of the alloy grains, thereby improving the hardness of the alloy and the corrosion resistance in chemical media.

[0017] Preferably, the weight ratio of the modified aluminum oxide, yttrium oxide and nickel oxide is (1.8-1.9):1:(0.12-0.15).

[0018] By adopting the above technical solution, when the modified aluminum oxide, yttrium oxide and nickel oxide are in a specific weight ratio, it helps to refine the grain structure of the alloy, improve the interface bonding inside the alloy, and thus improve the strength and hardness of the alloy.

[0019] Preferably, the particle size of the yttrium oxide is in the range of 12-15 nm.

[0020] By adopting the above technical solution, the selection of yttrium oxide with a smaller particle size will provide better sintering activity and mechanical properties.

[0021] In a second aspect, the present application provides a method for preparing an alloy with a high yttrium content using the following technical solution: A method for preparing an alloy with a high yttrium content comprises the following steps: uniformly mixing yttrium oxide, chromium oxide, modified aluminum oxide, nickel oxide, graphite powder, zinc stearate and manganese sulfide, transferring the mixture into a mold for forming, sintering the mixture at 1100-1130°C, and then performing oil immersion, shaping and cleaning to obtain an alloy with a high yttrium content.

[0022] By adopting the above technical scheme, the present application uses yttrium oxide and modified alumina as basic raw materials, adds chromium oxide, nickel oxide, graphite powder, zinc stearate and manganese sulfide according to a certain ratio, puts the raw materials in sequence, and reasonably controls the processing temperature to form an alloy with a high yttrium content, which has excellent corrosion resistance, wear resistance, high hardness and other characteristics.

[0023] In summary, this application has the following beneficial technical effects: 1. The present application uses yttrium oxide and modified alumina as raw materials for the alloy. The yttrium content in the prepared yttrium alloy is relatively high, which helps to promote grain refinement and improve the strength and densification of the alloy; the main component of graphite powder is carbon, which can improve the strength of the yttrium alloy; the addition of manganese sulfide can help the processing steps after the yttrium alloy is formed, and zinc stearate is used as a lubricant to reduce the friction between the material and the forming mold during the forming process of the yttrium alloy, thereby better improving the density of the yttrium alloy. Various raw materials cooperate with each other to form a yttrium alloy with higher hardness.

[0024] 2. The present application modifies alumina by adding titanium dioxide to the alumina, distributing the titanium dioxide on the surface of the alumina, reducing impurities and defects in the material after calcination, and combining the alumina containing titanium dioxide with yttrium oxide. The use of maleic anhydride grafted polypropylene and a silane coupling agent improves the interface bonding between the modified alumina and the yttrium aluminum alloy matrix, thereby improving the overall performance of the composite material. DETAILED DESCRIPTION

[0025] The present application is further described in detail below with reference to examples and comparative examples. Example

[0026] Example 1 A method for preparing an alloy with a high yttrium content comprises the following steps: 0.2g of yttrium oxide, 20g of chromium oxide, 10g of modified aluminum oxide, 30g of nickel oxide, 1g of graphite powder, 1g of zinc stearate and 0.5g of manganese sulfide are mixed evenly in a mixer, then transferred to a mold for forming, and then transferred to a sintering furnace, first preheating the mold at a temperature of 950°C for 20 minutes, then increasing the temperature and sintering at 1100°C for 2 hours to obtain a sintered part, immersing the sintered part in anti-rust oil for 1 minute, shaping it with an oil press, and then cleaning it with a hydrocarbon cleaning liquid to obtain an alloy with a high yttrium content. The particle size of the yttrium oxide is 15nm.

[0027] The preparation method of the modified alumina is as follows: 10g of titanium dioxide, 20g of alumina and 2g of dilute sulfuric acid are stirred at a stirring speed of 150r / min and a temperature of 70°C for 30min, 5g of sodium aluminate is added and stirred for 30min, calcined in a muffle furnace at a temperature of 1100°C for 10min, and then calcined in a calcining furnace at a temperature of 550°C for 2h, and after cooling, mixed and stirred with 10g of maleic anhydride grafted polypropylene and 5g of KH560 silane coupling agent, and transferred to an oven at a temperature of 80°C for drying for 24h to obtain modified alumina. Maleic anhydride grafted polypropylene is purchased from the Engineering Plastics Center of the Institute of Chemistry, Chinese Academy of Sciences, with a grafting rate of 1% and a melt index of 10g / min.

[0028] Example 2 A method for preparing an alloy with a high yttrium content comprises the following steps: 1.2g of yttrium oxide, 30g of chromium oxide, 20g of modified aluminum oxide, 50g of nickel oxide, 2g of graphite powder, 2g of zinc stearate and 1.5g of manganese sulfide are mixed evenly in a mixer, then transferred to a mold for forming, and then transferred to a sintering furnace, first preheating the mold at a temperature of 950°C for 20 minutes, then increasing the temperature and sintering at 1100°C for 2 hours to obtain a sintered part, immersing the sintered part in anti-rust oil for 1 minute, shaping it with an oil press, and then cleaning it with a hydrocarbon cleaning liquid to obtain an alloy with a high yttrium content. The particle size of the yttrium oxide is 15nm.

[0029] The preparation method of the modified alumina is as follows: 10g of titanium dioxide, 20g of alumina and 2g of dilute sulfuric acid are stirred at a stirring speed of 150r / min and a temperature of 70°C for 30min, 5g of sodium aluminate is added and stirred for 30min, calcined in a muffle furnace at a temperature of 1100°C for 10min, and then calcined in a calcining furnace at a temperature of 550°C for 2h, and after cooling, mixed and stirred with 10g of maleic anhydride grafted polypropylene and 5g of KH560 silane coupling agent, and transferred to an oven at a temperature of 80°C for drying for 24h to obtain modified alumina. Maleic anhydride grafted polypropylene is purchased from the Engineering Plastics Center of the Institute of Chemistry, Chinese Academy of Sciences, with a grafting rate of 1% and a melt index of 10g / min.

[0030] Example 3 A method for preparing an alloy with a high yttrium content comprises the following steps: 1g of yttrium oxide, 25g of chromium oxide, 15g of modified aluminum oxide, 40g of nickel oxide, 1.5g of graphite powder, 1.5g of zinc stearate and 1g of manganese sulfide are mixed evenly in a mixer, then transferred to a mold for forming, and then transferred to a sintering furnace, first preheating the mold at a temperature of 950°C for 20 minutes, then increasing the temperature and sintering at 1100°C for 2 hours to obtain a sintered part, immersing the sintered part in anti-rust oil for 1 minute, shaping it with an oil press, and then cleaning it with a hydrocarbon cleaning liquid to obtain an alloy with a high yttrium content. The particle size of the yttrium oxide is 15nm.

[0031] The preparation method of the modified alumina is as follows: 10g of titanium dioxide, 20g of alumina and 2g of dilute sulfuric acid are stirred at a stirring speed of 150r / min and a temperature of 70°C for 30min, 5g of sodium aluminate is added and stirred for 30min, calcined in a muffle furnace at a temperature of 1100°C for 10min, and then calcined in a calcining furnace at a temperature of 550°C for 2h, and after cooling, mixed and stirred with 10g of maleic anhydride grafted polypropylene and 5g of KH560 silane coupling agent, and transferred to an oven at a temperature of 80°C for drying for 24h to obtain modified alumina. Maleic anhydride grafted polypropylene is purchased from the Engineering Plastics Center of the Institute of Chemistry, Chinese Academy of Sciences, with a grafting rate of 1% and a melt index of 10g / min.

[0032] Example 4 A method for preparing an alloy with a high yttrium content, which is different from Example 3 in that: the preparation method of modified alumina is: 30g of titanium dioxide, 60g of alumina and 8g of dilute sulfuric acid are stirred for 30min at a stirring speed of 150r / min and a temperature of 70°C, and then 15g of sodium aluminate is added and stirred for 30min, and then calcined in a muffle furnace at a temperature of 1100°C for 10min, and then calcined in a calcining furnace at a temperature of 550°C for 2h, and after cooling, mixed and stirred with 20g of maleic anhydride grafted polypropylene and 15g of KH560 silane coupling agent, and transferred to an oven at a temperature of 80°C for drying for 24h to obtain modified alumina.

[0033] Example 5 A method for preparing an alloy with a high yttrium content, which is different from Example 3 in that: in the process of preparing modified alumina, an equal amount of maleic anhydride grafted polypropylene is replaced with modified maleic anhydride grafted polypropylene, wherein the preparation method of the modified maleic anhydride grafted polypropylene is as follows: 10g of maleic anhydride grafted polypropylene, 1g of diisopropylbenzene peroxide, 2g of dimethyl methyl phosphate and 5g of ethyl acetate are mixed and stirred, and then 4g of carbon fiber is added and mixed and stirred, ultrasonicated, stirred at a temperature of 80°C for 5h, filtered and then dried at a temperature of 80°C for 12h to obtain modified maleic anhydride grafted polypropylene.

[0034] Example 6 A method for preparing an alloy with a high yttrium content, which is different from Example 3 in that: in the process of preparing modified alumina, an equal amount of maleic anhydride grafted polypropylene is replaced with modified maleic anhydride grafted polypropylene, wherein the preparation method of the modified maleic anhydride grafted polypropylene is as follows: 20g of maleic anhydride grafted polypropylene, 3g of diisopropylbenzene peroxide, 8g of dimethyl methyl phosphate and 15g of ethyl acetate are mixed and stirred, and then 8g of carbon fiber is added and mixed and stirred, ultrasonicated, stirred at a temperature of 80°C for 5h, filtered and then dried at a temperature of 80°C for 12h to obtain modified maleic anhydride grafted polypropylene.

[0035] Example 7 A method for preparing an alloy with a high yttrium content, which is different from Example 6 in that the input amount of maleic anhydride grafted polypropylene is 17g, the input amount of carbon fiber is 5g, and the input amount of dimethyl methyl phosphate is 2.5g.

[0036] Example 8 A method for preparing an alloy with a high yttrium content, which is different from Example 6 in that the input amount of maleic anhydride grafted polypropylene is 19g, the input amount of carbon fiber is 5g, and the input amount of dimethyl methyl phosphate is 3g.

[0037] Example 9 A method for preparing an alloy with a high yttrium content, which is different from Example 8 in that: the input amount of titanium dioxide is 20g, the input amount of modified maleic anhydride grafted polypropylene is 16g, the input amount of sodium aluminate is 6g, and the input amount of aluminum oxide is 50g.

[0038] Example 10 A method for preparing an alloy with a high yttrium content, which is different from Example 8 in that: the input amount of titanium dioxide is 20g, the input amount of modified maleic anhydride grafted polypropylene is 18g, the input amount of sodium aluminate is 8g, and the input amount of aluminum oxide is 56g.

[0039] Embodiment 11 A method for preparing an alloy with a high yttrium content, which is different from Example 10 in that the input amount of modified aluminum oxide is 18g, the input amount of yttrium oxide is 1g, and the input amount of nickel oxide is 36g.

[0040] Example 12 A method for preparing an alloy with a high yttrium content, which is different from Example 10 in that the input amount of modified aluminum oxide is 19 g, the input amount of yttrium oxide is 1 g, and the input amount of nickel oxide is 45 g.

[0041] Comparative Example Comparative Example 1 A method for preparing an alloy with a high yttrium content, which is different from Example 3 in that an equal amount of modified alumina is replaced by alumina.

[0042] Comparative Example 2 A method for preparing an alloy with a high yttrium content is different from Example 3 in that: in the method for preparing the modified alumina, maleic anhydride grafted polypropylene is not added.

[0043] Comparative Example 3 A method for preparing an alloy with a high yttrium content is different from Example 3 in that: in the method for preparing modified alumina, the maleic anhydride grafted polypropylene is replaced with an equal amount of silicone resin, and the silicone resin is purchased from CE Company of the United States with a brand number of SFR100.

[0044] Comparative Example 4 A method for preparing an alloy with a high yttrium content is different from Example 3 in that: in the method for preparing modified alumina, the modified maleic anhydride grafted polypropylene is replaced with an equal amount of silicone resin, and the silicone resin is purchased from CE Company of the United States with a brand number of SFR100.

[0045] Performance testing: Corrosion resistance: The alloys prepared in Examples 1-12 and Comparative Examples 1-4 were subjected to a salt spray resistance test in a salt spray test chamber according to GB / T10125-1997.

[0046] Hardness: Using a Vickers hardness tester, a yttrium alloy disc with a diameter of 12.7 mm and a thickness of 3 mm is tested more than 3 times under a pressing force of 3 kg and a holding time of 15 s. The average value of the obtained data is the hardness of the yttrium alloy measured, in HV.

[0047] Tensile strength: The tensile strength of the alloys prepared in Examples 1-12 and Comparative Examples 1-4 was tested according to GB / T 228-2002.

[0048] According to the data comparison of Examples 1-4 and Comparative Examples 1-4, the present application uses yttrium oxide and modified alumina as raw materials for the alloy, and the yttrium content in the prepared yttrium alloy is relatively high, which helps to promote grain refinement and improve the strength and densification of the alloy; the main component of graphite powder is carbon, which can improve the strength of the yttrium alloy; the addition of manganese sulfide can help the processing steps after the yttrium alloy is formed, and zinc stearate is used as a lubricant to reduce the friction between the material and the forming mold during the forming process of the yttrium alloy, thereby better improving the density of the yttrium alloy, and various raw materials cooperate with each other to form a yttrium alloy with higher hardness. The present application modifies alumina, adds titanium dioxide to alumina, and distributes titanium dioxide on the surface of alumina. Impurities and defects in the material are reduced after calcination, and the alumina containing titanium dioxide is combined with yttrium oxide. The use of maleic anhydride grafted polypropylene and silane coupling agent improves the interface bonding between the modified alumina and the yttrium aluminum alloy matrix, thereby improving the overall performance of the composite material.

[0049] According to the data comparison of Examples 3-6, maleic anhydride grafted polypropylene can be used as an adhesive between yttrium aluminum alloy and carbon fiber to improve the bonding strength of the interface. Dimethyl methylphosphonate and ethyl acetate are used as solvents to help the mixing reaction of carbon fiber and maleic anhydride grafted polypropylene, so that the carbon fiber can be dispersed in the maleic anhydride grafted polypropylene, thereby allowing the carbon fiber to penetrate into the alloy component and improve the mechanical properties of the yttrium alloy.

[0050] According to the data comparison of Examples 6-8, when maleic anhydride grafted polypropylene, carbon fiber and dimethyl methyl phosphonate are in a specific weight ratio, maleic anhydride grafted polypropylene can form chemical bonds with the surfaces of aluminum oxide and yttrium oxide, enhance the interfacial bonding force between the raw materials, thereby improving the mechanical properties of the alloy. At the same time, maleic anhydride grafted polypropylene also bonds the carbon fiber and the alloy matrix, and dimethyl methyl phosphonate improves the bonding performance of the carbon fiber and the alloy matrix, thereby improving the overall performance of the alloy.

[0051] According to the data comparison of Examples 8-10, it can be obtained that when titanium dioxide, modified maleic anhydride grafted polypropylene, sodium aluminate and aluminum oxide are in a specific weight ratio, the four work together to improve the interface bonding inside the yttrium alloy and promote the refinement of the alloy grains, thereby improving the hardness of the alloy and the corrosion resistance in chemical media.

[0052] According to the data comparison of Examples 10-12, when the modified aluminum oxide, yttrium oxide and nickel oxide are in a specific weight ratio, it helps to refine the grain structure of the alloy, improve the interface bonding inside the alloy, and thus improve the strength and hardness of the alloy.

[0053] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An alloy with a high yttrium content, characterized in that: The invention comprises the following raw materials in parts by weight: 0.8-1.2 parts of yttrium oxide; 20-30 parts of chromium oxide; 10-20 parts of modified aluminum oxide; 30-50 parts of nickel oxide; 1-2 parts of graphite powder; 1-2 parts of zinc stearate; and 0.5-1.5 parts of manganese sulfide. The modified aluminum oxide is prepared from the following raw materials: titanium dioxide, aluminum oxide, dilute sulfuric acid, sodium aluminate, maleic anhydride grafted polypropylene and a silane coupling agent.

2. The alloy with high yttrium content according to claim 1, characterized in that: The preparation method of the modified alumina is as follows: 10-30 parts of titanium dioxide, 20-60 parts of alumina and 2-8 parts of dilute sulfuric acid are mixed and stirred, 5-15 parts of sodium aluminate are added, stirred and then calcined, after cooling, mixed and stirred with 10-20 parts of maleic anhydride grafted polypropylene and 5-15 parts of silane coupling agent, and dried to obtain the modified alumina.

3. The alloy with high yttrium content according to claim 2, characterized in that: The maleic anhydride grafted polypropylene is modified maleic anhydride grafted polypropylene. The preparation method of the modified maleic anhydride grafted polypropylene is as follows: 10-20 parts of maleic anhydride grafted polypropylene, 1-3 parts of diisopropylbenzene peroxide, 2-8 parts of dimethyl methyl phosphate and 5-15 parts of ethyl acetate are mixed and stirred, and then 4-8 parts of carbon fiber are added and mixed and stirred, ultrasonicated, filtered and then dried for 12 hours to obtain the modified maleic anhydride grafted polypropylene.

4. The alloy with high yttrium content according to claim 3, characterized in that: The weight ratio of the maleic anhydride grafted polypropylene, carbon fiber and dimethyl methyl phosphate is (3.4-3.8):1:(0.5-0.6).

5. The alloy with high yttrium content according to claim 2, characterized in that: The grafting rate of the modified maleic anhydride grafted polypropylene is 1-1.6%.

6. The alloy with high yttrium content according to claim 2, characterized in that: The weight ratio of the titanium dioxide, modified maleic anhydride grafted polypropylene, sodium aluminate and aluminum oxide is 1: (0.8-0.9): (0.3-0.4): (2.5-2.8).

7. The alloy with high yttrium content according to claim 3, characterized in that: The weight ratio of the modified aluminum oxide, yttrium oxide and nickel oxide is (18-19):1:(36-45).

8. The alloy with high yttrium content according to claim 1, characterized in that: The particle size of the yttrium oxide is in the range of 12-15 nm.

9. A method for preparing an alloy with a high yttrium content, characterized in that: The method for preparing the alloy with high yttrium content as described in any one of claims 1 to 9 comprises the following steps: yttrium oxide, chromium oxide, modified aluminum oxide, nickel oxide, graphite powder, zinc stearate and manganese sulfide are uniformly mixed and then transferred to a mold for forming, sintered at 1100-1130°C, and then oil-immersed, shaped and cleaned to obtain an alloy with high yttrium content.